KREATIFITAS DAN INOVASI UNTUK DAYA SAING USAHA PARIWISATA KREATIF - Rifki Rahmanda Putra; Dede Akhmad Nawawi; Rifqi Asy’ari (Jurnal Pariwisata Budaya: Jurnal Ilmiah Pariwisata Agama dan Budaya, 2023)
Competitiveness is still a problem for creative tourism entrepreneurs because the business world is growing following the time especially the uncertain conditions due to the Covid-19 pandemic. One of the fashion sub-sectors of the creative economy industry that is experiencing business competitiveness problems is the Rajut Binong Bandung Industry Center. The efforts made by the Rajut Binong Jati Bandung Industry Center as the creative tourism business to increase business competitiveness in the midst of the Covid-19 Pandemic by increasing creativity and innovation. This study aims to analyze how much influence creativity and innovation against creative tourism business competitiveness. This research using a descriptive approach with explanatory survey methods with a total of 71 sample respondents. The data analysis technique used is multiple regression with computer software tools for Statistical Product Service Solutions (SPSS) 24.0 for windows. The results showed the creativity and innovation have a fairly high and high influence on creative tourism business competitiveness. Creative tourism entrepreneurs need to continue to practice creativity by developing and improving new skills and ideas accompanied by strong encouragement or motivation. They also need to continue to innovate products, marketing, business models, and the services provided by the industry need to be developed to be ready to face competition.